6. (i) Show that (-100) – (5) is same as 100 + (-5)
(ii) Show that (-18) – [6 + (-1)] = [(-18) + 6] + (-1)
(ii) Show tha

Question

6. (i) Show that (-100) – (5) is same as 100 + (-5)
(ii) Show that (-18) – [6 + (-1)] = [(-18) + 6] + (-1)
(ii) Show that {(~72) + (-9)} = {(-20) + (-5)} = 2
199. If one integer is -9. find the other.​

in progress 0
Audrey 2 years 2021-06-22T17:16:26+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-06-22T17:17:27+00:00

    Answer:

    6. (i) Show that (-100) – (5) is same as 100 + (-5)

    (ii) Show that (-18) – [6 + (-1)] = [(-18) + 6] + (-1)

    (ii) Show that {(~72) + (-9)} = {(-20) + (-5)} = 2

    199. If one integer is -9. find the other

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )